ADSORPSI PENGOTOR MINYAK DAUN CENGKEH OLEH LEMPUNG TERAKTIVASI ASAM - Suarya, P. (Jurnal Kimia (Journal of Chemistry); Vol. 2, No. 1 Januari 2008)
Preparation, characterization and application of acid activated clays as adsorbents on the purification of clove leaves oil have been conducted. The effects of concentration of acid on the quality of the activated clay and on the adsorption performance of the prepared activated clay were also studied. Characterization of the activated clay was carried out using gas sorption analyzer and FTIR spectroscopy The results showed that the spesific surface area of the activated clays increases with increasing concentration of acid. At the concentration of acid of 0, 0.4, 0.8, 1.2, 1.6, and 2.0 M, the spesific surface areas were 48.27; 48.75, 54.31; 65.21; 62.91 and 51.86 m2/g, respectively. From the adsorption test, it was observed that the activated clay prepared with concentration acid of 1,2 M, showed the best performance. It’s was able to adsorp 284.2 mg of impurity and thus purify 40 ml of crude clove leaves oil.
Keywords: adsorbent, acid activated clay, clove leaves oil